2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6579976
|View full text |Cite
|
Sign up to set email alerts
|

Anti-slug control experiments using nonlinear observers

Abstract: Abstract-To prevent slug-flow on offshore oil production units, controlling a subsea pressure is the recommended solution. However, the subsea pressure is not often available as a measurement. The top-side pressure is usually measured but it is difficult to use for stabilizing control, because of its Right Half-Plane zero dynamics combined with nonlinearity. We have used the top-side pressure as measurement for different observers to estimate state variables of the system, and then used the estimated states fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…9 is 20%. This result is same as using a nonlinear observer and state feedback (Jahanshahi et al (2013)). …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…9 is 20%. This result is same as using a nonlinear observer and state feedback (Jahanshahi et al (2013)). …”
Section: Resultssupporting
confidence: 57%
“…However, the separation principle does not hold for nonlinear systems in general, and the closed-loop observer/controller is not 1 Corresponding author guaranteed to be stable for all conditions. Jahanshahi et al (2013) showed that a nonlinear observer fails in closedloop when using the subsea pressure as the measurement. In this work, we propose a nonlinear controller that uses the measurements of the system directly without using any observer.…”
Section: Introductionmentioning
confidence: 99%